1998
DOI: 10.1159/000015841
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Risk Factors Linked to Multiple Lacunar Infarcts

Abstract: Background: The pathogenesis of lacunar infarcts is still incompletely established. Data from the literature suggest that vascular risk factors differ among patients with multiple (MLI) and single lacunar infarcts (SLI). We reexamined this hypothesis using stricter inclusion criteria and a less selected study population. Methods: We evaluated 136 patients consecutively admitted for first-ever minor stroke to a general hospital with the characteristics of a community hospital. Vascular risk factors were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 16 publications
2
22
0
1
Order By: Relevance
“…For Lodder and Boiten [3], the established risk factors for lacunar infarcts are age, sex, hypertension, diabetes mellitus, ischemic heart disease, TIA, and current cigarette smoking. In our study, the frequencies of these risk factors are very similar to data collected in previous studies [3, 11]. …”
Section: Discussionsupporting
confidence: 90%
“…For Lodder and Boiten [3], the established risk factors for lacunar infarcts are age, sex, hypertension, diabetes mellitus, ischemic heart disease, TIA, and current cigarette smoking. In our study, the frequencies of these risk factors are very similar to data collected in previous studies [3, 11]. …”
Section: Discussionsupporting
confidence: 90%
“…21 Clinical or morphological evidence of hypertension was found in 97% of the cases in the same study of Fisher and in ÏŸ70% in other series. 17,18,22 Despite these findings, the role of hypertension in LI has been questioned, mainly because other causal factors for LI such as embolus of cardiac or carotid origin have been found recently. 3,4,6,7,9,16,23,24 Kappelle and van Gijn 7 revised 14 LI studies and found that 43% to 83% of the patients were hypertensive.…”
Section: Discussionmentioning
confidence: 99%
“…Lipohyalinosis, microatheroma, and, to a lesser extent, microembolism are considered the main causes of LI. At the occurrence of the first clinical lacunar stroke event, it has been observed 19,20 that when multiple (silent) lacunes are seen on imaging, both arterial hypertension and LA are more frequent than when a single (the only symptomatic) lacunar lesion is identified, suggesting that lipohyalinosis in the former case and microatheroma in the latter case might be selectively involved. In a longitudinal observation of 333 patients with a first-ever lacunar stroke, 21 mortality was ÏŸ1.5-fold higher (odds ratio [OR], 1.74; 95% CI, 1.01 to 3.01) and the stroke recurrence rate was 2-fold higher (OR, 2.09; 95% CI, 1.08 to 4.06) among the 104 patients with multiple silent lesions than among the 229 patients with a single lesion.…”
Section: La As a Predictor Of Ischemic Stroke Or Vascular Deathmentioning
confidence: 99%